2017
DOI: 10.1167/iovs.16-21191
|View full text |Cite
|
Sign up to set email alerts
|

Compromised Integrity of Central Visual Pathways in Patients With Macular Degeneration

Abstract: The results indicate that the RNFL and the white matter of the visual pathways are significantly altered in MD patients. Damage to the photoreceptors in MD leads to atrophy of the ganglion cell axons and to corresponding changes in microstructural properties of central visual pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
42
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(49 citation statements)
references
References 58 publications
7
42
0
Order By: Relevance
“…Future higher resolution studies might be able to report such damage. Our results are consistent with recent reports demonstrating that the white matter within the optic radiation is affected by AMD (Malania et al 2017). We go beyond these previous reports by utilizing an anatomically-informed method that allowed us to characterize the specificity of the relation between locations of retinal damage and the visual white matter.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Future higher resolution studies might be able to report such damage. Our results are consistent with recent reports demonstrating that the white matter within the optic radiation is affected by AMD (Malania et al 2017). We go beyond these previous reports by utilizing an anatomically-informed method that allowed us to characterize the specificity of the relation between locations of retinal damage and the visual white matter.…”
Section: Discussionsupporting
confidence: 90%
“…This suggests possible mechanisms for transsynaptic effects from the photoreceptors to the brain tissue. Indeed, our current results, previous ones (Malania et al 2017) as well as results demonstrating a reduction in cortical volume in AMD (Hernowo et al 2014;Prins et al 2016a, b) all provide strong convergent evidence that cell death within the retina could affect the brain tissue via transsynaptic degeneration (Prins et al 2016a;Haak et al 2016).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…A recent tractography-based study showed similar, significant reductions in optic tract FA as well as correlations between RNFL thickness and optic tract FA in participants with childhood or age-related macular degeneration. 37 These additional ophthalmologic measurements allow for a secondary level of verification of any microstructural abnormalities and provides a more precise mapping of the relationship between the various scales and measures of prethalamic microstructure integrity.…”
Section: Fellow and Affected Eye Optic Nerves In Amblyopiamentioning
confidence: 99%